The effects of myricitrin and vitamin E against reproductive changes induced by D-galactose as an aging model in female mice: An experimental study - Mina Omidi; Akram Ahangarpour; Seyed Ali Mard; Layasadat Khorsandi (International Journal of Reproductive BioMedicine, 2019)
Background Aging is accompanied by decreasing general function in the cells and tissues. D-galactose (D-gal) induces aging and plays a role in the pathogenesis of it. Myricitrin is a plant-derived antioxidant.